First report on simplified diagnostic criteria for pre-hypertension and hypertension in a national sample of adolescents from the Middle East and North Africa: the CASPIAN-III study - Roya Kelishadi; Ramin Heshmat; Gelayol Ardalan; Mostafa Qorbani; Mahnaz Taslimi; Parinaz Poursafa; Kasra Keramatian; Majzoubeh Taheri; Mohammad-Esmaeil Motlagh (Elsevier, 2014)
Objective: this study aimed to simplify the diagnostic criteria of pre-hypertension (pre-HTN) and hypertension (HTN) in the pediatric age group, and to determine the accuracy of these simple indexes in a nationally-representative sample of Iranian children and adolescents. Method: the diagnostic accuracy of the indexes of systolic blood pressure-to-height ratio (SBPHR) and diastolic BPHR (DBPHR) to define pre-HTN and HTN was determined by the area under the curve of the receiver operator characteristic curves. Results: the study population consisted of 5,738 Iranian students (2,875 females) with mean (SD) age of 14.7 (2.4) years. The prevalences of pre-HTN and HTN were 6.9% and 5.6%. The optimal thresholds for defining pre-HTN were 0.73 in males and 0.71 in females for SBPHR, and 0.47 in males and 0.45 in females for DBPHR, respectively. The corresponding figures for HTN were 0.73, 0.71, 0.48, and 0.46, respectively. In both genders, the accuracies of SBPHR and DBPHR in diagnosing pre-HTN and HTN were approximately 80%. Conclusions: BPHR is a valid, simple, inexpensive, and accurate tool to diagnose pre-HTN and HTN in adolescents. The optimal thresholds of SBPHR and DBPHR were consistent with the corresponding figures in other populations of children and adolescents with different racial and ethnic backgrounds. Thus, it is suggested that the use of these indexes can be generalized in programs aiming to screen elevated blood pressure in the pediatric age group. Resumo: Objetivo: este estudo visa simplificar os critérios de diagnóstico da pré-hipertensão (pré-HTA) e hipertensão (HTA) na faixa etária pediátrica e determinar a precisão desses índices simples em uma amostra nacionalmente representativa de crianças e adolescentes iranianos. Método: a precisão diagnóstica dos índices de relação pressão arterial sistólica/altura (RPASA) e RPAA diastólica (RPADA) para definir a pré-HTA e HTA foi determinada pela área sob as curvas de características de operação do receptor. Resultados: a população estudada contou com 5738 alunos iranianos (2875 meninas) com idade média (DP) de 14,7 (2,4) anos. A prevalência de pré-HTA e HTA foi 6,9% e 5,6%. Os limites ideais para a definição de pré-HTA foram 0,73 em meninos e 0,71 em meninas com relação à RPASA e 0,47 em meninos e 0,45 em meninas com relação à RPADA, respectivamente. Os valores correspondentes com relação à HTA foram 0,73, 0,71, 0,48 e 0,46, respectivamente. Em ambos os gêneros, a precisão de RPASA e RPADA no diagnóstico de pré-HTA e HTA foi de aproximadamente 80%. Conclusões: a RPAA é uma ferramenta válida, simples, barata e precisa no diagnóstico da pré-HTA e HTA em adolescentes. Os limites ideais de RPASA e RPADA foram compatíveis com os números correspondentes em outra população de crianças e adolescentes com diferentes históricos raciais e étnicos, assim, sugerimos que a utilização desses índices possa ser generalizada em programas de triagem com relação à PA elevada na faixa etária pediátrica. Keywords: Blood pressure, Screening, Pre-hypertension, Hypertension, Adolescence, Palavras-chave: Pressão sanguínea, Triagem, Pré-hipertensão, Hipertensão, Adolescência